SAT0414 Differences in clinical presentation by gender in colombian patients with spondyloarthropathies. (15th June 2017) - Alzate, MA; Vargas, F; Ramirez, F; Hernandez-Parra, D; Salazar-Uribe, JC; Ortiz-Salazar, P; Pineda, R; ,
Abstract : Background: Spondyloarthropathies (SpAs) are a group of auto-inflammatory diseases, with overlapping symptoms, that include ankylosing spondylitis (AS), psoriatic arthritis (PsA), undifferentiated spondyloarthritis (Und SpA), enteropathic arthritis, and reactive arthritis (1). Historically, SpAs have been viewed as diseases that predominantly affected men (2). Objectives: To analyze the influence of gender on disease patterns and therapeutic approach in a large cohort of Colombian patients with SpAs. Methods: A cross-sectional study was conducted in 621 patients with SpAs, in whom clinical and therapeutic characteristics were analyzed based on gender. Statistical association was examined by means of Chi-square tests, Mann-Whitney test, and logistic regression analyses. Results: The male-to-female ratio was 1, 1:1 in this cohort. Younger age at diagnosis was found in males. AS was the most frequent disease (54, 7%), followed by PsA (35, 7%), and undifferentiated SpA (9, 5%). The male gender was positively associated to the presence of AS (OR 2, 29 95%IC 1, 31–4, 04), radiographic sacroilitis (OR 3, 46 95%IC 1, 82–6, 56), HLAB27 positivity (OR 1, 95 95%IC 1, 31–2, 91), low back pain (OR 1, 85 95%IC 1, 34–2, 54) and axial involvement (OR 1, 98 95%IC 1, 42–2, 77). According to the therapeutic profile, female gender was positively associated to the use of conventional DMARD therapy (i.e., methotrexate (p=0, 03), leflunomide (p=0, 0057), chloroquine (p=0, 013)), while male patients were more associated to the use of biologic therapy. Conclusions: In this Colombian large sample with SpA, male patients have a younger onset of disease, higher proportion of axial involvement, HLAB27 positivity, evidence of radiographic sacroilitis and higher use of anti-TNF therapy. References: Roussou E, Sultana S. Spondyloarthritis in women: differences in disease onset, clinical presentation, and Bath Ankylosing Spondylitis Disease Activity and Functional indices (BASDAI and BASFI) between men and women with spondyloarthritides. Clin Rheumatol. 2011;30(1):121–7. Ibn Yacoub Y, Amine B, Laatiris A, Hajjaj-Hassouni N. Gender and disease features in Moroccan patients with ankylosing spondylitis. Clin Rheumatol. 2012;31(2):293–7. Disclosure of Interest: None declared